Loss of miR-192-5p initiates a hyperglycolysis and stemness positive feedback in hepatocellular carcinoma - Gu, Yuanzhuo; Ji, Fubo; Liu, Niya; Zhao, Yongzhi; Wei, Xiyang; Hu, Shiyuan; Jia, Wei; Wang, Xin Wei; Budhu, Anuradha; Ji, Juling; Zhao, Bin; Rössler, Stephanie; et al. (Journal of experimental & clinical cancer research, 2020)
Emerging studies revealed that cancer stem cells (CSCs) possessed peculiar metabolic properties, which however remained largely unknown in hepatocellular carcinoma (HCC). Genetic silencing of liver-abundant miR-192-5p was a key feature for multiple groups of CSC-positive HCCs. We thus aimed to investigate essential metabolic features of hepatic CSCs via using HCCs with miR-192-5p silencing as a model.